2019
DOI: 10.6060/mhc190446r
|View full text |Cite
|
Sign up to set email alerts
|

Pyropheophorbide-Fullerene Dyad: Synthesis and Photochemical Properties

Abstract: The methylpyropheophorbide-fullerene[60] dyad was synthesized by 1,3-dipolar cycloadditions of the corresponding azomethine ylide to C 60 (Prato reaction). Using the mass spectrometric method with soft matrix-activated ionization it was possible to achieve a significant reduction in fragmentation processes by the retro-Diels-Alder reaction, which allows to reliably detect the presence of polyadducts of azomethine ylide cycloadditions to fullerene. The use of gel permeation chromatography under conditions of we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 28 publications
(37 reference statements)
0
22
0
Order By: Relevance
“…[8][9][10][11] Such protocols serve to adapt the target product to the practical applications in various elds of medicine, biochemistry or optoelectronics. 13 Molecular structures of some chlorophyll dyes that are used as functional components of PVC are shown in Fig. 1.…”
Section: Molecules and Visible Absorption Spectramentioning
confidence: 99%
“…[8][9][10][11] Such protocols serve to adapt the target product to the practical applications in various elds of medicine, biochemistry or optoelectronics. 13 Molecular structures of some chlorophyll dyes that are used as functional components of PVC are shown in Fig. 1.…”
Section: Molecules and Visible Absorption Spectramentioning
confidence: 99%
“…76 Rybkin et al (Institute of Problems of Chemical Physics, Chernogolovka, Russia) modified the MAI approach by guiding the matrix:analyte sample on a wire into the sub-AP region of the mass spectrometer where the ionization proceeds to characterize dyes. 77 Murray's group (Louisiana State University, Baton Rouge, LA, USA) measured particle sizes after laser ablation of LSI and other matrices, 78,79 introduced a pulsed valve ionization method in which one of the MAI matrices is knocked off a surface in close proximity to the heated mass spectrometer inlet, 80 and used MAI matrices as co-matrix for tissue analyses. 81 Halvorsen et al (University of Oslo, Oslo, Norway) demonstrated the utility of single reaction monitoring for quantitative proteomics using MAI on a triple quadrupole mass spectrometer.…”
Section: Introductionmentioning
confidence: 99%
“…Wilkins et al (University of Arkansas, Fayetteville, AR, USA) used MAI and LSI for FTICR measurements 65 and applied MAI to bacterial analyses in both positive and negative ion detection mode 76 . Rybkin et al (Institute of Problems of Chemical Physics, Chernogolovka, Russia) modified the MAI approach by guiding the matrix:analyte sample on a wire into the sub‐AP region of the mass spectrometer where the ionization proceeds to characterize dyes 77 . Murray's group (Louisiana State University, Baton Rouge, LA, USA) measured particle sizes after laser ablation of LSI and other matrices, 78,79 introduced a pulsed valve ionization method in which one of the MAI matrices is knocked off a surface in close proximity to the heated mass spectrometer inlet, 80 and used MAI matrices as co‐matrix for tissue analyses 81 .…”
Section: Introductionmentioning
confidence: 99%
“…Gel permeation chromatography in pyridine led to a quantitative separation of the reaction mass (with the concentration of the reaction mass of 1 mg/ml) into three main fractions: product M 3 , product M 2 , and unsubstituted fullerene with "traces" of pyropheophorbide. 8 First, the products of this reaction were analyzed using MALDI. MALDI-TOF mass spectra were taken on a Bruker Autoflex II mass spectrometer (nitrogen laser with k ¼ 337 nm, TOF resolution -18000 (FWHM)) with pyridine as the solvent and a-cyano-4-hydroxycinnamic acid (CHCA) as the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Gel permeation chromatography in pyridine led to a quantitative separation of the reaction mass (with the concentration of the reaction mass of 1 mg/ml) into three main fractions: product M 3 , product M 2 , and unsubstituted fullerene with “traces” of pyropheophorbide. 8…”
Section: Introductionmentioning
confidence: 99%